2014
DOI: 10.2528/pier13080806
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Filtering and Unwrapping Sar Interferometric Phase Based on Nonlinear Phase Model

Abstract: Abstract-This paper presents a new efficient algorithm of filtering and unwrapping phase images for interferometric synthetic aperture radar (InSAR) based on nonlinear phase model. First, we analyzed the statistical and signal properties of interferometric phase, and proposed the concept of nonlinear phase model. The model of reflecting topographic contour is used to approximate the interferometric phase variation occuring over the local window. And the lower amplitude bound of the principal vector is decided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This minimization requires a high calculation cost. To solve this problem, a lot of methods have been proposed such as unwrapping methods [4]- [10], filtering methods [11]- [17], local registration methods [18]- [21] and methods using polarimetric interferometric SAR (PolInSAR) [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…This minimization requires a high calculation cost. To solve this problem, a lot of methods have been proposed such as unwrapping methods [4]- [10], filtering methods [11]- [17], local registration methods [18]- [21] and methods using polarimetric interferometric SAR (PolInSAR) [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…Interferometric synthetic aperture radar (SAR, InSAR) is one of the main methods for generating digital elevation models (DEMs) and monitoring terrain deformation [ 1 , 2 ]. In recent years, many countries have developed their own SAR satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, overseas and domestic research on SBAS InSAR focused on improving the identification and selection of highly coherent pixels (Costantini, Falco, Malvarosa, & Minati, 2009;Ferretti, Novali, Zan, Prati, & Rocca, 2008), increasing the accuracy and efficiency of phase unwrapping (Heshmat, Tomioka, & Nishiyama, 2011;Huang & Wang, 2014), effectively separating error phase components (Li, Fielding, & Cross, 2006), constructing and robustly estimating deformation models (Jiang, Liu, & Tao, 2016;Zhai, Liu, Tao, & Xin, 2017) and extending new applications (Costantini, Mouratidis, Schiavon, & Francesco, 2016;Esmaeili, Motagh, & Hooper, 2017;Liu et al, 2014), etc. However, in practical applications, it was found that the quality and quantity of multi-temporal differential interferogram series seriously affected the monitored surface deformation results of StaMPS-based SBAS InSAR.…”
Section: Introductionmentioning
confidence: 99%